2016
DOI: 10.5152/balkanmedj.2016.141103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MIF -173 G/C Polymorphism in Turkish Patients with Ankylosing Spondylitis

Abstract: Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease mainly affecting the spine and sacroiliac joints. Macrophage migration inhibitory (MIF) factor is a regulatory cytokine that inhibits random immune cell migration. MIF gene promoter polymorphisms play a role in the progression of several inflammatory disorders. Aims: To investigate the relationship between the MIF gene -173 G/C single-nucleotide polymorphism (SNP) and AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hypermethylation of both p14 ARF and p16 INK4a was found in normal colonic mucosal tissues of patients with UC, as well in the precancerous lesions, suggesting that UC patients with this particular inflammatory genotype of MIF may be at a higher risk for developing colonic cancer (128). This rs755622C genotype association was also observed in patients with IBD and in Chinese patients with psoriasis, but not in Turkish patients with AS (97,98,129). Despite that, the authors have suggested that the time of onset and the duration of AS still might be affected by rs755622C allele (129).…”
Section: Suggested Novel Hypothesismentioning
confidence: 83%
See 1 more Smart Citation
“…Hypermethylation of both p14 ARF and p16 INK4a was found in normal colonic mucosal tissues of patients with UC, as well in the precancerous lesions, suggesting that UC patients with this particular inflammatory genotype of MIF may be at a higher risk for developing colonic cancer (128). This rs755622C genotype association was also observed in patients with IBD and in Chinese patients with psoriasis, but not in Turkish patients with AS (97,98,129). Despite that, the authors have suggested that the time of onset and the duration of AS still might be affected by rs755622C allele (129).…”
Section: Suggested Novel Hypothesismentioning
confidence: 83%
“…This rs755622C genotype association was also observed in patients with IBD and in Chinese patients with psoriasis, but not in Turkish patients with AS (97,98,129). Despite that, the authors have suggested that the time of onset and the duration of AS still might be affected by rs755622C allele (129). However, this hypothesis still needs to be proven in the laboratory, along with testing for MIF-rs755622C allele in more patients with early-onset jSpA.…”
Section: Suggested Novel Hypothesismentioning
confidence: 93%
“…Two databases were about atopic dermatitis (AD) [25,26], Henoch-Schonlein purpura nephritis (HSPN) [27], and Henoch-Schonlein purpura (HSP) [28]. The other nine diseases were inquired in single databases, including ankylosing spondylitis (AS) [29], primary gout [30], primary biliary cirrhosis (PBC) [24], psoriasis (Ps) [31], systemic lupus erythematosus (SLE) [32], Vogt-Koyanagi-Harada syndrome (VKH) [33], adult still disease (AOSD) [34], Behcet's disease (BD) [35], and scleroderma (SD) [36]. The areas of the studies involved in the present analysis were Asian, Europe, and North America.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%